Electronic Circuit Analysis. - Rao, B. Visvesvara; Rajeswari, K. Raja.; Pantulu, P. Chalam (2011)
Electronic Circuit Analysis is designed to serve as a textbook for a two semester undergraduate course on electronic circuit analysis. It builds on the subject from its basic principles over fifteen chapters, providing detailed coverage on the design and analysis of electronic circuits.
4.27 Output Characteristics for an N-Channel Enhancement-Mode MOSFET.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2018. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books